2017
DOI: 10.1002/ece3.2999
|View full text |Cite
|
Sign up to set email alerts
|

Dispersal corridors for plant species in the Poyang Lake Basin of southeast China identified by integration of phylogeographic and geospatial data

Abstract: Measuring the dispersal of wildlife through landscapes is notoriously difficult. Recently, the categorical least cost path algorithm that integrates population genetic data with species distribution models has been applied to reveal population connectivity. In this study, we use this method to identify the possible dispersal corridors of five plant species (Castanopsis tibetana, Schima superba, Cyclocarya paliurus, Sargentodoxa cuneata, Eomecon chionantha) in the Poyang Lake Basin (PLB, largely coinciding with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“…Using least-cost path calculations, we confirmed that a major south–north dispersal corridor occurred along the plains and hills on the eastern side of the Poyang Lake Basin, and two east–west dispersal corridors occurred along the hills in the central Jiangxi Province and north of the Mufu Mountains ( Figures 8D–F ). Our investigations supported the conclusions of Fan et al (2017), which showed that stronger population connectivity occurred in the eastern Poyang Lake Basin corridor for five plant species in subtropical China, and connections also occurred between the eastern and the western populations across the basin. However, the corridors detected in this study occupied a much lower elevation than those identified by Fan et al (2017) (e.g., the Wuyi Mountains and the Yushan Mountains), implying that lowlands are important for the migration of plants that prefer a habitat at low elevation regions.…”
Section: Discussionsupporting
confidence: 90%
“…Using least-cost path calculations, we confirmed that a major south–north dispersal corridor occurred along the plains and hills on the eastern side of the Poyang Lake Basin, and two east–west dispersal corridors occurred along the hills in the central Jiangxi Province and north of the Mufu Mountains ( Figures 8D–F ). Our investigations supported the conclusions of Fan et al (2017), which showed that stronger population connectivity occurred in the eastern Poyang Lake Basin corridor for five plant species in subtropical China, and connections also occurred between the eastern and the western populations across the basin. However, the corridors detected in this study occupied a much lower elevation than those identified by Fan et al (2017) (e.g., the Wuyi Mountains and the Yushan Mountains), implying that lowlands are important for the migration of plants that prefer a habitat at low elevation regions.…”
Section: Discussionsupporting
confidence: 90%
“…Although there are numerous mountains or hills in east China, they seldom exceed 2000 m above sea level and thus rarely function as barriers (but see Sun et al, 2014a ). On the contrary, many mountain ranges (such as the Nanling Mountains, the Wuyi Mountains and the Luoxiao Mountains) in east STC played a role as dispersal corridors during the Quaternary climate oscillations, facilitating gene exchange among isolated populations ( Fan et al, 2017 ; Tian et al, 2018 ). In addition, when those dispersal corridors facilitated inter-/postglacial range expansions, a south-north decreasing trend of AGD might be observed because the lower genetic divergence at higher latitudes may result from a genetic drift or bottleneck effect during recolonization from refugia.…”
Section: Discussionmentioning
confidence: 99%
“…A species’ paleodistribution can be determined through an integrated phylogeographic and species distribution modeling (SDM) approach even in the absence of fossil records. The phylogeographic method that analyzes the spatial distribution of genealogical lineages is a powerful tool for inferring the demographic history of plant species (Fan et al, 2017). Such a study can provide important insights into the effects of paleoclimatic change on the current geographic distribution and genetic structure of species (Avise, 2000; Byrne, 2007; Dalmaris et al, 2015).…”
Section: Introductionmentioning
confidence: 99%